Identification of key biomarkers related to fibrocartilage chondrocytes for osteoarthritis based on bulk, single-cell transcriptomic data - Pan, Bailin; Yao, Peixiu; Ma, Jinjin; Lin, Xuanhao; Zhou, Laixi; Lin, Canzhen; Zhang, Yufeng; Lin, Bendan; Lin, Chuangxin (Frontiers in Immunology, 2024)
IntroductionOsteoarthritis (OA) is a prevalent joint disease that severely impacts patients’ quality of life. Due to its unclear pathogenesis and lack of effective therapeutic targets, discovering new biomarkers for OA is essential. Recently, the role of chondrocyte subpopulations in OA progression has gained significant attention, offering potential insights into the disease. This study aimed to explore the role of fibrocartilage chondrocytes (FC) in the progression of OA and identify key biomarkers related to FC.MethodsWe analyzed single-cell ribonucleic acid sequencing (scRNA-seq) data from samples of OA and normal cartilage, focusing on FC. Microarray data were integrated to identify differentially expressed genes (DEGs). We conducted functional-enrichment analyses, including Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO), and used weighted gene co-expression network analysis (WGCNA) and the least absolute shrinkage and selection operator (LASSO) algorithm to select biomarkers. A novel risk model for OA was constructed using these biomarkers. We then built a transcription factor (TF)–gene interaction network and performed immunohistochemistry (IHC) to validate protein expression levels of these biomarkers in cartilage samples.ResultsThe study identified 545 marker genes associated with FC in OA. GO and KEGG analyses revealed their biological functions; microarray analysis identified 243 DEGs on which functional-enrichment analysis were conducted. Using WGCNA and LASSO, we identified six hub genes, on the basis of which we constructed a risk model for OA. In addition, correlation analysis revealed a close association between Forkhead Box (FoxO)-mediated transcription and these these biomarkers. IHC showed significantly lower protein levels of ABCA5, ABCA6 and SLC7A8 in OA samples than in normal samples.ConclusionThis study used a multi-omics approach to identify six FC-related OA biomarkers (BCL6, ABCA5, ABCA6, CITED2, NR1D1, and SLC7A8) and developed an exploratory risk model. Functional enrichment analysis revealed that the FoxO pathway may be linked to these markers, particularly implicating ABCA5 and ABCA6 in cholesterol homeostasis within chondrocytes. These findings highlight ABCA family members as novel contributors to OA pathogenesis and suggest new therapeutic targets.